2013
DOI: 10.1128/jcm.01083-13
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a New Automated Homogeneous PCR Assay, GenomEra C. difficile, for Rapid Detection of Toxigenic Clostridium difficile in Fecal Specimens

Abstract: bWe evaluated a new automated homogeneous PCR assay to detect toxigenic Clostridium difficile, the GenomEra C. difficile assay (Abacus Diagnostica, Finland), with 310 diarrheal stool specimens and with a collection of 33 known clostridial and nonclostridial isolates. Results were compared with toxigenic culture results, with discrepancies being resolved by the GeneXpert C. difficile PCR assay (Cepheid). Among the 80 toxigenic culture-positive or GeneXpert C. difficile assay-positive fecal specimens, 79 were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
3
1
Order By: Relevance
“…The sensitivity of GenomEra PCR has been reported to be similar to those of several other nucleic acid amplification-based methods (32,33), thus being a valid molecular test for our comparison study. The specificity of the GenomEra PCR test in our study was better than what has previously been reported (32)(33)(34). The sensitivities obtained in our study from clinical specimens are also in line with the analytical sensitivities of the mariPOC (2018-02 user's manual) and TechLab (2016/07 user's manual) tests stated by the manufacturers: 0.7 ng/ml versus 0.8 ng/ml for GDH, 0.1 ng/ml versus 0.63 ng/ml for toxin A, and 0.1 ng/ml versus 0.16 ng/ml for toxin B, respectively.…”
Section: Discussioncontrasting
confidence: 82%
“…The sensitivity of GenomEra PCR has been reported to be similar to those of several other nucleic acid amplification-based methods (32,33), thus being a valid molecular test for our comparison study. The specificity of the GenomEra PCR test in our study was better than what has previously been reported (32)(33)(34). The sensitivities obtained in our study from clinical specimens are also in line with the analytical sensitivities of the mariPOC (2018-02 user's manual) and TechLab (2016/07 user's manual) tests stated by the manufacturers: 0.7 ng/ml versus 0.8 ng/ml for GDH, 0.1 ng/ml versus 0.63 ng/ml for toxin A, and 0.1 ng/ml versus 0.16 ng/ml for toxin B, respectively.…”
Section: Discussioncontrasting
confidence: 82%
“…After retesting, all except 1 gave positive results. In the only published evaluation of this assay, Hirvonen et al found only 1 borderline result from 310 specimens tested with GenomEra (0.3%) (16). After retesting, this specimen, which was positive for toxigenic culture, yielded a negative result.…”
mentioning
confidence: 99%
“…Eight studies (23%) used an enrichment broth before plating onto a solid agar [19,22e24,32,43,58,62]. Toxigenicity was confirmed by PCR (15/32, 47%) [21,23,29,33e35,37,51e57,70], CCNA (9/32, 28%) [7,8,22,24,43,47,58,61,62], toxin EIA (7/32, 22%) [19,30,32,38,40,69,71] or both PCR and CCNA (1/32, 3%) [26]. Blinding (index test interpreted without knowledge of reference test or vice versa) was reported in 8 (14%) of 56 studies.…”
Section: Quality Assessmentmentioning
confidence: 99%